Arduino based humidity and temperature sensor logger for environment monitoring: article - Miskon, Nur Wahida (2013)
This project is to develop a Humidity and Temperature Sensor Logger and Monitoring using Arduino. The device is used to measure and store data of temperature and relative humidity of a particular area. Monitoring is performed automatically using this system so that no manual operation is applied to the instruments during whole period of observation. The three pins on the sensor connect the two devices. The pins are inserted into the Arduino through the twowire digital serial interface, and digital data is transmitted here. The Arduino will be programmed with the specific Arduino software. After the setup a coding is inputted to Arduino boot loader chip and the sensor is ready to be run and measure. It will read out the humidity and temperature values which then are stored into the SD card and displayed on the LCD. Based on the sensor, the accuracy of the temperature should be within ±2⁰C, while the relative humidity is ±5%. Real time clock (RTC) is used to record time for every data taken and 10kΩ resistor as a pull up for the sensor. The red and yellow LED will indicate whether data taken is saved into SD card or not.